2016
DOI: 10.7146/tfss.v12i23.22895
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects in chronic pain conditions. Can placebo components enhance the efficacy of active treatments?

Abstract: Skyt, I. & Vase, L. (2015). Placebo effects in chronic pain conditions. Can placebo components enhance the efficacy of active treatments?, Tidsskrift for Forskning i Sygdom og Samfund, nr. 23,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
(97 reference statements)
0
3
0
1
Order By: Relevance
“…Additionally, within neuropathic pain syndromes, the presence of certain symptom characteristics can also influence the response rate (the number of patients that show a positive response). For instance, studies that include symptoms of hyperalgesia have been suggested to have among the largest placebo responses [ 48 ]. This highlights how variable individual responses can be, even within similar conditions and the need to carefully consider how diagnostically homogenous a population has to be to demonstrate treatment efficacy [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, within neuropathic pain syndromes, the presence of certain symptom characteristics can also influence the response rate (the number of patients that show a positive response). For instance, studies that include symptoms of hyperalgesia have been suggested to have among the largest placebo responses [ 48 ]. This highlights how variable individual responses can be, even within similar conditions and the need to carefully consider how diagnostically homogenous a population has to be to demonstrate treatment efficacy [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accurate estimates relative to potential placebo responses are required to inform study design in terms of power calculations and statically analysis. Systematic reviews highlight significant variation in placebo responses between different types of neuropathic pain [ 47 ] and further variation relative to different sensory characteristics [ 48 ]. Stratification of patients by sensory phenotype at least for pain populations has been suggested, which could improve treatment selection and outcomes by allowing for mechanistically informed treatment selection [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, dicho efecto también está mediado por neurotransmisores asociados al dolor, pues se ha asociado con la liberación de opioides endógenos, serotonina y dopamina (De La Fuente y Stoessl, 2002). De hecho, se ha planteado la posibilidad de aprovechar el efecto placebo analgésico para mejorar los resultados de un tratamiento farmacológico activo (Skyt y Vase, 2016), y dado que el dolor es una experiencia subjetiva y que sólo el paciente puede medir, y que la musicoterapia es un tratamiento no farmacológico libre de riesgos, este puede implementarse independientemente de si se produce un efecto placebo o no siempre y cuando así lo desee el paciente para aliviar su dolor. Además, el dolor suele ser un síntoma o una consecuencia de una enfermedad que en muchas ocasiones sí debe tratarse con farmacoterapia real, por lo que una terapia alternativa para reducir la nocicepción como lo es la musicoterapia podría reducir el consumo de analgésicos, aminorando los riesgos de interacciones farmacológicas, aún si se trata de un efecto placebo.…”
Section: Discussionunclassified
“…Ethical issues remain [ 13 , 86 ] regarding deception and the fact that placebos rarely cure, although a recent study indicated open placebo without deception to provide additional effectiveness over and above normal care in attenuating symptoms in low back pain patients [ 87 ]. Notwithstanding, clear boundaries would be imperative with a focusing of such care on ostensibly non-life threatening conditions or the sequelae of other conditions such as chronic pain [ 88 ]. In addition, embracing such a different view of what legitimate treatment constitutes, may be a challenge not only in some of the manual therapeutic professions but also to medicine itself.…”
Section: The Science Of Clinician Mediated Innate Healing: Why Patienmentioning
confidence: 99%